Efektivitas Gamifikasi dalam Meningkatkan Motivasi dan Hasil Belajar Siswa Sekolah Dasar pada Mata Pelajaran Matematika - Rahman Ansori; Ikbal Sananta; Rijalul Huda (PGSD UNU NTB, 2025)
This study aims to analyze the effectiveness of gamification in improving the motivation and learning outcomes of elementary school students in mathematics. The background of the study indicates that low student interest and participation are major obstacles to academic achievement. Gamification is used as an innovative strategy by integrating game elements, challenges, rewards, and feedback to encourage student engagement. The research method uses a mixed approach with a field experimental design. Data were collected through observations, achievement tests, motivation questionnaires, and interviews. Participants consisted of fourth to sixth grade students divided into experimental and control groups. The results showed that gamification significantly increased students' intrinsic and extrinsic motivation as well as active participation in learning. Students were more enthusiastic, confident, and able to solve math problems better. In addition, collaboration and communication skills were also developed through team-based activities. The teacher's role proved crucial in managing the game and adjusting the difficulty level. These findings indicate that gamification is effective in improving learning outcomes while creating an interactive, enjoyable, and sustainable learning experience.